Κανθαροειδείς κοτύλες και εξάλειπτρα από το αρχαίο νεκροταφείο Θέρμης Νομού Θεσσαλονίκης (CH. TSOUGARIS, Gray Kantharoid cotylae and exaleiptra from the ancient cemetery of modern Thermi, Thessaloniki) - Τσούγγαρης, Χαράλαμπος (Μακεδονικά, 2011)
Ch. Tsougaris,  Gray kantharoid cotylae and exaleiptra from the ancientcemetery of modern Thermi, Thessaloniki.Gray, wheel-made pottery with a polished surface, although not an unusualfind during excavation of late-archaic cemeteries in Central Macedonia, has sofar received little attention, apart from a number of milestone articles by prof.M. Tiverios, who studied the Sindos finds.This short study is hoped to shed some light to the problems of chronology,origin, expansion, use and production technology of the two most commonshapes, exaleiptra and kantharoid cotylae. A group of fifteen pots is examined,unearthed during the first years of excavation at the ancient cemetery of modern Thermi, east of Thessaloniki. Several of these can be dated by accompanying vases, imported from Attica or Corinth, or by similarities to otherdated gray wares.Among nine exaleiptra there is one example of each one of the angular,biconical, and flattened types, while a forth type, with a continuous profile, ismore usual. The latter evolves (within the time-span of ca. 540-500 µ.C.) froma squat vase with a rounded, incurving lip and an up-tilted handle, to a highervase with a broken, vertical lip and an horizontal handle.The six kantharoid cotylae presented, belong to a variation of the kantharos shape, which has no forerunners in earlier Macedonian pottery. Althoughthe origin of this variation can be traced back to the Bronze Age, it is arguedthat it entered Macedonia around 550 B.C. through direct contacts with N.E.Peloponnese, or with the Corinthian colony of Potidaea and in the graves ittakes the place of other large drinking vessels. The production center(s) of thisware must have been on the coast of the Thermaic Gulf, where it appears inlarge numbers, but it also reaches Upper Macedonia to the west and Pelagoniato the north. Contrary to what is generally accepted, production of this grayware seems to have been demanding, as it called for high skills during polishing, high temperatures during firing and an excellent control of a reducingatmosphere in the kiln.